2014
DOI: 10.1371/journal.pone.0114404
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ablation and Resection (CARe) as an Effective Parenchymal Sparing Treatment for Extensive Colorectal Liver Metastases

Abstract: BackgroundCombined intra-operative ablation and resection (CARe) is proposed to treat extensive colorectal liver metastases (CLM). This multicenter study was conducted to evaluate overall survival (OS), local recurrence-free survival (LRFS), hepatic recurrence-free survival (HRFS) and progression-free survival (PFS), to identify factors associated with survival, and to report complications.Materials and MethodsFour centers combined retropectively their clinical experiences regarding CLM treated by CARe. CLM ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 30 publications
1
46
1
1
Order By: Relevance
“…In the study published in 2014, Evrard et al 50 combined PSLR with RFA in 288 patients, five-year overall survival was 37%, compared to 39% for the 18 patients that underwent resection combined with local ablation in our study. These outcomes demonstrate that multiple simultaneous LPSLRs are feasible and may be preferred over single major resection in a substantial portion of patients.…”
Section: Discussioncontrasting
confidence: 41%
“…In the study published in 2014, Evrard et al 50 combined PSLR with RFA in 288 patients, five-year overall survival was 37%, compared to 39% for the 18 patients that underwent resection combined with local ablation in our study. These outcomes demonstrate that multiple simultaneous LPSLRs are feasible and may be preferred over single major resection in a substantial portion of patients.…”
Section: Discussioncontrasting
confidence: 41%
“…The 5-year overall survival rate in this group is about 20% 209,210 , an impressive figure for metastatic disease. One clinical trial has used a perioperative FOLFOX protocol in this group of patients and showed an improvement in PFS, but no significant difference in overall survival compared with surgery alone 201 .…”
Section: Managementmentioning
confidence: 80%
“…,51 However, the improved response among patients with KRAS WT tumors indicates a potential predictive biomarker role for KRAS when evaluating patients for combination HAI and SYS chemotherapy.Additional methods to increase conversion to resectability can be used in conjunction with HAI and SYS chemotherapy. We employed surgical techniques such as intraoperative ablation and two-stage liver resections to achieve complete resection in patients with complex, bilobar metastases [52][53][54][55][56]. PVE can also performed for patients who are deemed unresectable due to lack of sufficient volume in the future liver remnant; however, PVE does not address the issue of irresectability due to excessive tumor burden or unfavorable tumor location relative to major vessels or biliary structures 57.…”
mentioning
confidence: 99%